Morphophysiological and molecular characterization of millet (Panicum miliaceum L.) varieties for crop improvement in Western Europe - Massimo Vischi; Nicola Zorzin; Maria Bernhart; Johanna Winkler; Dipak Santra; Carla Pappalardo; Stefano Marchetti (CABI Agriculture and Bioscience)
Abstract Background Global warming and issues in favour of a more sustainable agriculture suggest a reconsideration of minor cereals in European agrosystems. Compared to other summer crops, proso millet has a remarkable drought resistance and could be used to improve crop rotation and biodiversity. Proso millet is also increasingly sought by industry to produce novel foods such as those designed for coeliac patients. In this study, a thorough characterization of 11, commercially available, proso millet (Panicum miliaceum L.) varieties was carried out as a preliminary step for crop reintroduction and breeding in Western Europe. Methods The cultivars under evaluation were introduced from Austria, Poland, Russia, and the USA (University of Nebraska–Lincoln). Plants were grown at Udine (NE Italy) and Gleisdorf (Styria, Austria), under greenhouse and field conditions, respectively. Yield components and a range of morphophysiological characters were recorded in both locations. In parallel, 85 SSR markers were tested on DNA samples extracted from randomly chosen plants of each variety and the 12 responsive markers used to genotype the whole variety set. Results Morphometric analyses showed that varieties have several diverging phenotypic traits and architectures. In all instances, yields recorded at field level were much lower than potential yields. In this respect, US selections were comparable to earlier developed European varieties, suggesting that breeding for an increased adaptation is the keystone for a stable reintroduction of millet in Western Europe. Molecular analyses uncovered remarkably low genetic differences and heterozygosity levels within cultivars, confirming millet as an essentially autogamous species; in contrast, large genetic distances were noted among cultivars selected in different environments. Results of SSR genotyping combined with those originating from phenotypic analyses indicated possible crosses to source the genetic variability necessary for selection. Conclusions This study enabled the identification of cultivars that could be used to revitalize the crop in Western Europe and to produce genetically variable hybrid progenies exploitable by breeding.